On performance of multi hop CDMA wireless sensor networks with correlated interferers. (1st January 2013) - Datta, Uma; Sahu, Pradyumna Kumar; Kundu, Sumit
Multi-hop communication in wireless sensor networks helps in attaining broader coverage and distributes the use of power throughout the hops. This paper evaluates the end-to-end performance of a CDMA-based static multi-hop wireless sensor network (WSN) with layered architecture in shadowed environment. End-to-end probability of outage, bit error rate (BER), average energy consumption, and the associated delay for successful delivery of a packet from a source to a sink, separated by a fixed distance, are evaluated for different number of hops. An interference model for multi-hop is presented considering correlation amongst shadow faded interferers. Two different information delivery mechanisms are investigated using regenerative relays with and without error correction capability. Energy requirement, and delay for successful delivery of a data packet from a source to sink is evaluated for each packet transmission scheme considering a suitable energy model and compared under several conditions of node density, packet length, and number of hops between source and sink. Optimal hop count is estimated on the basis of energy requirement and delay for successful delivery of data from a source to sink. Analytical results are supported by simulation.